Habitat use, reproductive traits and social interactions in a stream-dweller treefrog endemic to the Brazilian Cerrado - Nali, Renato C. [UNESP]; Prado, Cynthia P. A. [UNESP] (Brill Academic Publishers, 2012)
The richest anuran fauna is found in the Neotropics, but the natural history of most species is unknown. Bokermannohyla ibitiguara is a stream-dweller treefrog endemic to the Brazilian Cerrado and classified as Data Deficient by the IUCN. Herein we describe the species' reproductive biology. Fieldwork was conducted from August 2010 to July 2011. Reproductive activity occurred from October to June and was positively correlated with air temperature, humidity, and monthly rainfall. Individuals were observed only in gallery forests at the margins of streams and males used various kinds of substrates as calling sites. Males did not aggregate in specific parts of the streams and spatial distance between males was higher in the dry season. Males and females did not differ in length, but females without mature oocytes were lighter than males. The reproductive investment (gonad mass/body mass) of males was 0.29% and that of females was 20.26%. Female ovaries contained a mean of 202 +/- 75 mature oocytes with a mean diameter of 1.96 +/- 0.16 mm. We describe, for the first time for the genus, a complex courtship behaviour and also male-male fight and satellite behaviour. The Cerrado is probably the most threatened savanna in the world, having been intensively modified over the last decades. Endemic species associated to gallery forests, such as B. ibitiguara, are highly vulnerable to habitat alterations. Thus, our study provides important data on the species' biology, which might be useful for conservation practices, but also to investigate taxonomic and phylogenetic relationships in this genus.
Keywords: Bokermannohyla ibitiguara; calling sites; courtship behaviour; Hylidae; temporal distribution